2014
DOI: 10.1186/2051-3933-2-2
|View full text |Cite
|
Sign up to set email alerts
|

Elephant movement closely tracks precipitation-driven vegetation dynamics in a Kenyan forest-savanna landscape

Abstract: BackgroundThis study investigates the ranging behavior of elephants in relation to precipitation-driven dynamics of vegetation. Movement data were acquired for five bachelors and five female family herds during three years in the Marsabit protected area in Kenya and changes in vegetation were mapped using MODIS normalized difference vegetation index time series (NDVI). In the study area, elevations of 650 to 1100 m.a.s.l experience two growth periods per year, while above 1100 m.a.s.l. growth periods last a ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
93
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(96 citation statements)
references
References 70 publications
3
93
0
Order By: Relevance
“…; Bohrer et al . ). These findings highlight an important, yet unresolved, question of whether green‐wave surfing is a common behaviour among migrating ungulates.…”
Section: Introductionmentioning
confidence: 97%
“…; Bohrer et al . ). These findings highlight an important, yet unresolved, question of whether green‐wave surfing is a common behaviour among migrating ungulates.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, a powerful predictive migration model for the migratory zebra, Equus burchelli antiquorum, was developed using NDVI data to evaluate how their timing and pace of movement is affected by spatio-temporal changes in the environment (Bartlam-Brooks et al, 2013). Another example also showed that elephants tracked an intermediate value of NDVI in the Marsabit protected area in Kenya, corresponding to the "surfing the green wave" hypothesis (Bohrer et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In order to implement effective conservation and management plans, a greater understanding is required about elephant movements across large areas and over long periods (Breuer et al, ; Loarie, Aarde, & Pimm, ). Both the distribution and movement patterns of African savannah elephants ( Loxodonta africana Blumenbach, 1797) have been related to land cover type (Loarie et al, ; Young, Ferreira, & van Aarde, ), weather (i.e., temperature and rainfall; Birkett, Vanak, Muggeo, Ferreira, & Slotow, ; Bohrer et al, ) and elevation, slope and the presence of water bodies (natural or artificial; Graham, Douglas‐Hamilton, Adams, & Lee, ). These natural features interact with human infrastructures such as fences or human settlements (Buij et al, ; Loarie et al, ), which shape elephant movement patterns.…”
Section: Introductionmentioning
confidence: 99%